Prevalence of Psychological Distress Among Quarantined People in Trivandrum District During the COVID-19 Pandemic: A Cross-sectional Study - S Prakash, Sneha; Sabu, Sneha; Raghavan, Jayaprakash; Sujatha, Chintha (International Journal of Medical Students, 2022)
Background: Quarantine is considered the most effective way to reduce the transmission of an infectious disease. The outbreak of coronavirus disease-19 (COVID-19) in 2020 led to many people being quarantined at various locations. The literature shows that people who undergo quarantine face psychological problems, such as depression, anxiety and stress. The aim of this study was to estimate the prevalence of psychological issues among quarantined people during the COVID-19 pandemic. Methods: This cross-sectional study was conducted in Trivandrum, Kerala, India. Adults aged 18 years and above who underwent quarantine in the area of the Pangappara Medical Health Centre were included. A semi-structured questionnaire and the Depression Anxiety Stress Scale-21 were administered to those who had given their informed consent. Quantitative variables were summarized using mean, standard deviation, and categorical variables with proportions. Significance of association was tested using the chi-square tests. Results: There were 143 participants included in the study. It was found that 23.8% had depressive symptoms, 14% had anxiety symptoms and 16.8% had significant stress. People from the age group of 26-40 years (p = 0.017), people from the higher educated group (p = 0.010) and non-resident Keralites (Keralites who were residing elsewhere and returned to Kerala during the pandemic) (p = 0.041) had the highest prevalence of depressive symptoms. Conclusion: People who undergo quarantine face many psychological issues. The health care system should provide adequate psychosocial support to quarantined people suffering from psychological problems. Health care workers should undergo appropriate training to provide these supports.